Root Reinforcement Improved Performance, Productivity, and Grain Bioactive Quality of Field-Droughted Quinoa (Chenopodium quinoa) - Toubali, Salma; Ait-El-Mokhtar, Mohamed; Boutasknit, Abderrahim; Anli, Mohamed; Ait-Rahou, Youssef; Benaffari, Wissal; Ben-Ahmed, Hela; Mitsui, Toshiaki; Baslam, Marouane; Meddich, Abdelilah (Frontiers in Plant Science, 2022)
Modern agriculture is facing multiple and complex challenges and has to produce more food and fiber to feed a growing population. Increasingly volatile weather and more extreme events such as droughts can reduce crop productivity. This implies the need for significant increases in production and the adoption of more efficient and sustainable production methods and adaptation to climate change. A new technological and environment-friendly management technique to improve the tolerance of quinoa grown to maturity is proposed using native microbial biostimulants (arbuscular mycorrhizal fungi; AMF) alone, in the consortium, or in combination with compost (Comp) as an organic matter source under two water treatments (normal irrigation and drought stress (DS)). Compared with controls, growth, grain yield, and all physiological traits under DS were significantly decreased while hydrogen peroxide, malondialdehyde, and antioxidative enzymatic functions were significantly increased. Under DS, biofertilizer application reverted physiological activities to normal levels and potentially strengthened quinoa’s adaptability to water shortage as compared to untreated plants. The dual combination yielded a 97 % improvement in grain dry weight. Moreover, the effectiveness of microbial and compost biostimulants as a biological tool improves grain quality and limits soil degradation under DS. Elemental concentrations, particularly macronutrients, antioxidant potential (1,1-diphenyl-2-picrylhydrazyl radical scavenging activity), and bio-active compounds (phenol and flavonoid content) were accumulated at higher levels in biofertilizer-treated quinoa grain than in untreated controls. The effects of AMF+Comp on post-harvest soil fertility traits were the most positive, with significant increases in total phosphorus (47 %) and organic matter (200 %) content under drought conditions. Taken together, our data demonstrate that drought stress strongly influences the physiological traits, yield, and quality of quinoa. Microbial and compost biostimulation could be an effective alternative to ensure greater recovery capability, thereby maintaining relatively high levels of grain production. Our study shows that aboveground stress responses in quinoa can be modulated by signals from the microbial/compost-treated root. Further, quinoa grains are generally of higher nutritive quality when amended and inoculated with AMF as compared to non-inoculated and compost-free plants.